Mitochondrial proteomes of porcine kidney cortex and medulla: foundation for translational proteomics - Tuma, Zdenek; Kuncova, Jitka; Mares, Jan; Matejovic, Martin (Clinical and experimental nephrology, 2016)
BACKGROUND: Emerging evidence has linked mitochondrial dysfunction to the pathogenesis of many renal disorders, including acute kidney injury, sepsis and even chronic kidney disease. Proteomics is a powerful tool in elucidating the role of mitochondria in renal pathologies. Since the pig is increasingly recognized as a major mammalian model for translational research, the lack of physiological proteome data of large mammals prompted us to examine renal mitochondrial proteome in porcine kidney cortex and medulla METHODS: Kidneys were obtained from six healthy pigs. Mitochondria from cortex and medulla were isolated using differential centrifugation and proteome maps of cortical and medullar mitochondria were constructed using two-dimensional gel electrophoresis (2DE). Protein spots with significant difference between mitochondrial fraction of renal cortex and medulla were identified by mass spectrometry. RESULTS: Proteomic analysis identified 81 protein spots. Of these spots, 41 mitochondrial proteins were statistically different between renal cortex and medulla (p < 0.05). Protein spots containing enzymes of beta oxidation, amino acid metabolism, and gluconeogenesis were predominant in kidney cortex mitochondria. Spots containing tricarboxylic acid cycle enzymes and electron transport system proteins, proteins maintaining metabolite transport and mitochondrial translation were more abundant in medullar mitochondria. CONCLUSION: This study provides the first proteomic profile of porcine kidney cortex and medullar mitochondrial proteome. Different protein expression pattern reflects divergent functional metabolic role of mitochondria in various kidney compartments. Our study could serve as a useful reference for further porcine experiments investigating renal mitochondrial physiology under various pathological states.
Keywords: Models, Animal; Mitochondria; Male; Sus scrofa; dřeň ledvin; Translational Research, Biomedical; 2D gelová elektroforéza; tandemová hmotnostní spektrometrie; Kidney Cortex; translační biomedicínský výzkum; Electrophoresis, Gel, Two-Dimensional; mužské pohlaví; Pig kidney; Kidney Medulla; mitochondriální proteiny; proteomika; Mitochondrial Proteins; kůra ledviny; Two-dimensional electrophoresis; Animals; ženské pohlaví; zvířata; modely u zvířat; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Proteomics; Tandem Mass Spectrometry; Female; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; mitochondrie